On the Pivotal Role of Veterinarians in the Fight Against Avian Influenza A (H5N1) Virus, COVID-19 and Future Pandemics - Giovanni Di Guardo (Pathogens)
An interesting article recently published in Science highlights the actions, the strategies and the tools through which the potential emergence of a new pandemic caused by the avian influenza A (H5N1) virus could be efficiently counteracted [...]